1983
DOI: 10.1172/jci110858
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of somatomedin and insulin receptors in the human fetus.

Abstract: A B S T R A C T This study examines the ontogenesis of somatomedin and insulin receptors in man. Particulate plasma membranes were prepared by ultracentrifugation from various tissues removed from fetuses after abortion and classified as <17, 17-25, and >25 cm in length. The binding of iodinated insulinlike growth factors 1 (IGF-1) and 2 (IGF-2), somatomedin A (SMA), multiplication-stimulating activity (MSA), and insulin was examined at the different ages.In the liver, cross-reaction studies revealed separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
72
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(76 citation statements)
references
References 30 publications
4
72
0
Order By: Relevance
“…These correlations are expected from the findings of increased serum IGFBP-1 and IGFBP-2 levels by Western ligand blotting and decreased IGF-I in IUGR newborns (21,27,43). IGF-I has been reported to inhibit IGFBP-1 production in Hep G-2 cells (51), which, similar to the fetal liver but unlike the adult liver, display high expression of the type 1 IGF receptor (2,52). Because the fetal human liver is the major production site for IGFBP-1 and IGFBP-2 (14, 15), IGF-I may regulate their expression in the human fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These correlations are expected from the findings of increased serum IGFBP-1 and IGFBP-2 levels by Western ligand blotting and decreased IGF-I in IUGR newborns (21,27,43). IGF-I has been reported to inhibit IGFBP-1 production in Hep G-2 cells (51), which, similar to the fetal liver but unlike the adult liver, display high expression of the type 1 IGF receptor (2,52). Because the fetal human liver is the major production site for IGFBP-1 and IGFBP-2 (14, 15), IGF-I may regulate their expression in the human fetus.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I and IGF-I1 are important paracrinelautocrine fetal growth factors with potential actions a s early as during human embryogenesis (1)(2)(3)(4)(5). In addition, IGF-I may be an important endocrine growth factor regulating generalized…”
mentioning
confidence: 99%
“…We also have found that a synthetic human H1 relaxin analog (deletion of the C-terminal Lys-Arg-Ser-Leu of B chain) could displace the binding of 32P-relaxin with a dissociation constant very similar to that of H2 relaxin (unpublished results of PLO). The crossreactive binding of these peptide hormones to other members of the receptor family raises the possibility that relaxin may display tissue-specific binding to additional receptor(s), possibly of the insulin receptor family (34)(35)(36)(37)(38), with either higher or lower affinities. Thus, the discovery of these relaxin binding sites in the brain and heart may uncover a complex biology in several organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for IGF-I are found in various tissues early in gestation (3), and fetal tissues seem to have enhanced sensitivity to IGF-I compared with later in life (4). Using cordocenteses, it has been possible to determine the "normal" range of IGF-I in fetal serum and to define a positive correlation between serum concentration of IGF-I and gestational age (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%